Determinant Faktor Keberhasilan Penerapan Sistem Pengukuran Kinerja Sektor Publik - Edward Fazri; Trisnowati Josiah; Esti Utami Pratiwi; Aprilia Risma Ainasya; Dahlia Andesti (Universitas Sang Bumi Ruwa Jurai, 2022)
This study aims to examine the factors that influence the implementation of the Performance Measurement System and its effect on the Performance of Regional Apparatus Organizations in Cilegon City. The sample in this study were officials involved in the strategic planning process at the Regional Work Equipment Organization in Cilegon City. The sampling technique used was purposive sampling and data collection was done by distributing questionnaires directly to respondents. Analysis of the research data using the Partial Least Square method.The results of this study reveal that Information, Organizational Goals and Targets and Organizational Commitment have a positive and significant effect on the implementation of the performance measurement system. In addition, this study also succeeded in finding that the Performance Measurement System had a positive and significant effect on Organizational Performance.